Cytotoxic T lymphocyte antigen 4‐immunoglobulin G is a potent adjuvant for experimental allergen immunotherapy. (11th March 2013) - Maazi, H.; Shirinbak, S.; den, L. E.; Fallarino, F.; Volpi, C.; Nawijn, M. C.; van, A. J. M.
Summary Allergen‐specific immunotherapy (SIT) is the only treatment for allergic diseases that targets allergen‐specific T helper type 2 (Th2) cells, which are the cause of the disease. There is an unmet requirement for adjuvants that increase the clinical efficacy of SIT allowing application of lower doses of the allergen, thereby reducing the risk of anaphylactic reactions. Cytotoxic T lymphocyte antigen 4–immunoglobulin (CTLA‐4–Ig) has been shown to induce immunological tolerance in autoimmunity and allograft transplantation by blocking T cell co‐stimulation and induction of the immunoregulatory enzyme indoleamine 2, 3 dioxygenase (IDO). Previously, we showed that CTLA‐4–Ig treatment at the time of allergen inhalation induced tolerance to subsequent allergen exposure in a mouse model of asthma. In this study, we test the hypothesis that CTLA‐4–Ig acts as an adjuvant for experimental SIT. We evaluated the adjuvant effects of CTLA‐4–Ig on SIT in a mouse model of ovalbumin‐driven asthma. We used both wild‐type and IDO‐deficient mice to assess the role of IDO in the adjuvant effects of CTLA‐4–Ig. Co‐administration of CTLA‐4–Ig strongly increased SIT‐induced suppression of airway hyperreactivity (AHR), specific IgE in serum, airway eosinophilia and Th2 cytokine levels. Moreover, we found that CTLA‐4–Ig, as an adjuvant for SIT, is equally effective in IDO‐deficient and wild‐type mice, demonstrating that the effect of CTLA‐4–Ig is independent of IDO expression. We show that CTLA‐4–Ig acts as a potent adjuvant to augment the therapeutic effects of SIT. As the adjuvant activity of CTLA‐4–Ig is independent of IDO, we conclude that it acts by blocking CD28‐mediated T cell co‐stimulation.